Composting of Dry Leaves and Household Kitchen Wastes Using Rotary Drum Biocomposter - Auriyani, Wika Atro; Fahni, Yunita; Saputri, Desi Riana; Mawaddah, Nurul; Fajar, Mutiara; Novita, Ella; Asmarani, Wulan; Asfari Ahmad, Raden Fattah (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
According to data from the National Waste Management Information System (SIPSN) for 2020, the largest pile of waste according to waste sources in Lampung Province comes from household waste, namely 42%. Along the Dusun II road in Way Hui Village, almost every day the community burns leaf litter in their yards, which causes pollution. In addition, according to data from the Central Statistics Agency (BPS) for 2020, agriculture in Lampung is the 15th highest, namely 90.48%. However, in its management, the majority of agriculture and plantations in Lampung use inorganic fertilizers to increase the quality and quantity of crops. This problem can be overcome by using organic waste as compost to gradually improve soil quality and reduce the volume of household kitchen waste. The Rotary Drum Biocomposter is a simple and inexpensive composter for processing kitchen and household organic waste in a sustainable manner. To speed up the composting process, a bioactivator is added as a decomposer. Bioactivators can be made by utilizing rice washing water waste and papaya fruit waste, which are rich in nutrients and can increase the macronutrients of the compost. The composting method used in this research is aerobic composting. This tool aims to educate the surrounding community that waste can be turned into valuable goods with good management, thereby creating a healthy environment and profitable business opportunities.